COVID-19 Beliefs Among Hispanic and Latinx Virginians: An Application of the Health Belief Model - Martinez Gonzalez, Andrea; Reynolds-Tylus, Tobias; Galarreta-Aima, Diana; Alemán, Carlos G. (Frontiers in Communication, 2022)
Introduction. COVID-19 disproportionally affects U.S. Hispanic and Latinx individuals. Guided by the health belief model, we examined COVID-19 beliefs among Hispanic and Latinx adults in Virginia. Method. Respondents (n = 414) were Hispanic and/or Latinx adults in Virginia recruited via Qualtrics panel between May and September 2021. Approximately two-thirds completed the survey in English (63.0%), and one-third completed the survey in Spanish (37.0%). Results. Most respondents self-reported as vaccinated (72%). Vaccinated respondents reported greater perceived severity and susceptibility to COVID-19 than unvaccinated respondents. Perceived benefits and barriers to vaccination were identified among vaccinated and unvaccinated respondents, respectively. Among unvaccinated respondents, self-efficacy was greater for individuals who planned to get vaccinated compared with those who did not or were unsure. For cues-to-action, vaccinated and unvaccinated respondents identified credible sources and channels for COVID-19 information. Conclusion. Our results highlight several opportunities and challenges to promoting COVID-19 awareness and vaccination among Hispanic and Latinx adults.